Budidaya Kentang Ramah Lingkungan Melalui Aplikasi Pupuk Organik Shisako - I.A.PUTRI DARMAWATI; GEDE WIJANA (Fakultas Pertanian Universitas Udayana, 2012)
Field experiment was conducted at Antapan village, Baturiti, Tabanan Regency. The experimentaim was to study the optimals of Shisako organic fertilizer dosage for growth and yield of potato. Theexperiment utilized Randomized Complete Design, one factor with six rated of Shisako organic fertilizerdosage treatments. The dosage treatments were: D0 = 0 ton/ha, D1 = 2,5 ton/ha, D2 = 5 ton/ha, D3 =7,5 ton/ha, D4 = 10 ton/ha and D5 = 12,5 ton/ha. The results showed that Shisako organic fertilizerdosage was highly significantly different to plant height, leaf number, leaf area index, tubers number perhill, tuber fresh weight per hill and fresh tubers weight per hectare than control. The optimum of Shisakofertilizer dosage treatment for microtuber Granola of potato cultivars from this research was found at6,08 ton/ha with the maximum wet weight tubers was 5,13 ton/ha.